Survey of the knowledge, attitude and practice of Nigerian surgery trainees to HIV-infected persons and AIDS patients (2002)
Background: The incidence of HIV infection and AIDS is rising in Nigeria. Surgeons are at risk of occupationally acquired infection as a result of intimate contact with the blood and body fluids of patients. This study set out to determine the knowledge, attitude and risk perception of Nigerian surgery residents to HIV infection and AIDS. Methods: A self-administered postal questionnaire was sent to all surgery trainees in Nigeria in 1997. Results: Parenteral exposure to patients' blood was reported as occurring 92.5% times, and most respondents assessed their risk of becoming infected with HIV as being moderate at 1-5%. The majority of the respondents were not aware of the CDC guidelines on universal precautions against blood-borne pathogens. Most support a policy of routinely testing all surgical patients for HIV infection but 76.8% work in centers where there is no policy on parenteral exposure to patients' blood and body fluids. Most (85.6%) do not routinely use all the protective measures advocated for the reduction of transmission of blood borne pathogens during surgery, with the majority ascribing this to non-availability. Most want surgeons to be the primary formulators of policy on HIV and surgery while not completely excluding other stakeholders. Conclusions: The study demonstrates the level of knowledge, attitude and practice of Nigerian surgery trainees in 1997 and the need for policy guidelines to manage all aspects of the healthcare worker (HCW), patients, and HIV/AIDS interaction.